2009
DOI: 10.1007/s10551-009-0026-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Society’s Awareness of Women: Media-Portrayed Idealized Images and Physical Attractiveness

Abstract: visual consumption, physical attractiveness, beauty, idealized image,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…These results are in contrast to most marketing strategies that invariably recommend associating a product with a successful, physically attractive individual. [21][22][23][24][25][26][27] Hence looking at pictures of an individual may actually personalise the description and evoke a more sympathetic outcome than simply asking participants to rate a hypothetical person based purely on a written description.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in contrast to most marketing strategies that invariably recommend associating a product with a successful, physically attractive individual. [21][22][23][24][25][26][27] Hence looking at pictures of an individual may actually personalise the description and evoke a more sympathetic outcome than simply asking participants to rate a hypothetical person based purely on a written description.…”
Section: Main Findingsmentioning
confidence: 99%
“…[18][19][20] By comparison, marketing strategies for commercial products invariably associate their product with positive images and avoid associating it with any negative images. [21][22][23][24][25][26][27] Hence the study aimed to look at the effect of viewing pictures of dysmorphic people with intellectual disabilities on stigmatised attitudes.…”
mentioning
confidence: 99%
“…33,34 Looking at an attractive picture of a man with Down syndrome actually reduced stigmatised attitudes and this is supported by most marketing strategies that invariably recommend associating a product with a successful, physically attractive individual rather than an unappealing image. [21][22][23][24][25][26][27] Methods to reduce the stigma of mental illness…”
Section: Discussionmentioning
confidence: 99%
“…invariably associate their product with positive images and avoid associating it with any negative images. [21][22][23][24][25][26][27] Hence our study looked at the effect of viewing pictures of people with intellectual disability and dysmorphic facial features on stigmatised attitudes.…”
mentioning
confidence: 99%
“…Although there exists substantial literature exploring the influence of celebrity-inspired, mediated images and advertisements on women (e.g., Choi & Rifon, 2007;Eisend & Langner, 2010;Lin & Yeh, 2009), few studies have examined cosmetic surgery advertising content in particular, and just one study has focused on agency and medical discourse. Ring (1999) conducted a qualitative comparative analysis of two Australian magazines about cosmetic surgery to assess the convergence of editorial and advertising content within each magazine and found that cosmetic surgeons both advertised and provided editorial content within issues.…”
Section: Cosmetic Surgery Advertisingmentioning
confidence: 99%